2017
DOI: 10.4330/wjc.v9.i5.407
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure after myocardial infarction in the era of primary percutaneous coronary intervention: Mechanisms, incidence and identification of patients at risk

Abstract: Myocardial infarction (MI) remains the most common cause of heart failure (HF) worldwide. For almost 50 years HF has been recognised as a determinant of adverse prognosis after MI, but efforts to promote myocardial repair have failed to translate into clinical therapies. Primary percutaneous coronary intervention (PPCI) has driven improved early survival after MI, but its impact on the incidence of downstream HF is debated. The effects of PPCI are confounded by the changing epidemiology of MI and HF, with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
132
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(136 citation statements)
references
References 84 publications
2
132
1
1
Order By: Relevance
“…Our study demonstrated that only PCSK9 inhibitor pre-treatment helped to improve the PV loop parameters ( Figure 6A Introduction of reperfusion therapy in post-myocardial infarction treatment has increased the number of patients surviving the initial infarct; however, the proportion of patients developing heart failure has increased. 21 This may in part be caused by the significant reperfusion injury sustained as blood flow is restored to the heart. A rapid increase in oxygen increases free radical synthesis in mitochondria to yield ROS, which subsequently cause many downstream cellular physiology effects, and leads to an overall change in cardiac function.…”
Section: Pcsk9 Inhibitor Pre-treatment Improved Left Ventricular Fumentioning
confidence: 99%
“…Our study demonstrated that only PCSK9 inhibitor pre-treatment helped to improve the PV loop parameters ( Figure 6A Introduction of reperfusion therapy in post-myocardial infarction treatment has increased the number of patients surviving the initial infarct; however, the proportion of patients developing heart failure has increased. 21 This may in part be caused by the significant reperfusion injury sustained as blood flow is restored to the heart. A rapid increase in oxygen increases free radical synthesis in mitochondria to yield ROS, which subsequently cause many downstream cellular physiology effects, and leads to an overall change in cardiac function.…”
Section: Pcsk9 Inhibitor Pre-treatment Improved Left Ventricular Fumentioning
confidence: 99%
“…AMI remains the most common cause of heart failure that is a determinant of adverse prognosis in the STEMI patients [22]. PCI has improved early survival after STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…PCI has improved early survival after STEMI. However, its impact on the incidence of following heart failure is debated [22]. On the basis of available literature, it is estimated that despite successful PCI and restoring flow in IRA, unfavorable remodeling of the LV and heart failure development can be noticed in 30% of patients during early and long-term follow-up [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Low socioeconomic status, and its correlates, including low educational attainment, are independent risk factors for CVD events, including non-fatal myocardial infarction and sudden cardiac death, in both men and women [28]. Given that myocardial infarction is the primary cause of HF worldwide [29], and CVD remains the leading cause of death globally, it is likely that poverty and environmental factors, collectively known as social determinants of health, similarly influence the risk for incident HF. Pathways that may help explain these associations include lower access to quality care and a higher burden of smoking, obesity, and physical inactivity among individuals of lower socioeconomic status [30].…”
Section: Discussionmentioning
confidence: 99%